Synthesis of ZnO nanowires by pulsed laser deposition in furnace - Son, Hyo Jeong; Jeon, Kyung Ah; Kim, Chang Eun; Kim, Jong Hoon; Yoo, Kyung Hwa; Lee, Sang Yeol (ELSEVIER SCIENCE BV, 2007)
ZnO nanowires were fabricated on Au coated (0 0 0 1) sapphire substrates by using a pulsed Nd:YAG laser with a ZnO target in furnace. ZnO nanowires have various sizes and shapes with a different substrate position inside a furnace. The length and the diameter of these ZnO nanowires were around 3-4 mu m and 120-200 nm, respectively, confirmed by scanning electron microscopy (SEM). The diameter control of the nanowires was achieved by varying the position of substrates. The ultraviolet emission of nanowires from the near band-edge emission (NBE) was observed at room temperature. The formation mechanism and the effect of different position of substrates on the structural and optical properties of ZnO nanowires are discussed. (c) 2007 Published by Elsevier B.V.
Keywords: GROWTH; NANORODS; NANOTUBES; POWDERS